Process of Fabricating Hyaluronic Acid-Based Milli-to-Microneedles Using the Bi-Directional Drawing Method - Joon-Koo Kang; Kihak Lee; Yein Choi; Se-Gie Kim; Bonghwan Kim (Micro)
Microneedles (MNs) have emerged as a promising tool for pain-free drug delivery, offering an alternative to traditional syringe-based methods. Among various types of MNs, dissolving microneedles fabricated from hyaluronic acid (HA) have gained attention due to their biocompatibility and ability to deliver drugs with minimal discomfort. However, conventional HA MN fabrication techniques often limit needle lengths to a few hundred micrometers, which is insufficient for deeper drug penetration. This study introduces a novel fabrication method using bidirectional drawing lithography to extend the length of HA-based MNs. By adjusting the viscosity of HA solutions and employing a controlled pulling process, we demonstrate the feasibility of producing MNs with lengths ranging from millimeters to micrometers. An average height of 15 mm and tip diameters of approximately 80 μm were successfully produced. This advancement enhances the potential of HA MNs for transdermal drug delivery and interstitial fluid sampling.